Pengaruh Kompetensi Pedagogik dan Kedisiplinan Guru terhadap Kinerja Guru di SD Negeri 04 Jaya Pura - Lia Emerda; Yasir Arafat; Nurlina Nurlina (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and analyze: (1) The relationship between Pedagogical Competence and teacher performance; (2) The relationship between Teacher Discipline and teacher performance; and (3) The relationship between Pedagogical Competence and Teacher Discipline together on teacher performance at SD Negeri 04 Jaya Pura. Pedagogical competence includes the teacher's ability to design, implement, and evaluate the learning process, while teacher discipline involves the teacher's commitment and consistency in carrying out tasks. The research method used is a quantitative approach with a case study design. Data were obtained through questionnaires distributed to all teachers at SD Negeri 04 Jaya Pura and analyzed using linear regression techniques to measure the influence of two independent variables on teacher performance. The results of the study indicate that both pedagogical competence and teacher discipline have a significant influence on teacher performance. Teachers with high pedagogical competence are more able to manage the learning process effectively, while teacher discipline directly affects the consistency and quality of their performance in the school environment. This study concludes that improving teacher pedagogical competence and discipline is very important to improve teacher performance, which in turn will have a positive impact on the quality of education.